1972
DOI: 10.1126/science.176.4034.536
|View full text |Cite
|
Sign up to set email alerts
|

Splitbrain Monkeys: Cerebral Control of Ipsilateral and Contralateral Arm, Hand, and Finger Movements

Abstract: The connections of the descending pathways in the monkey suggest that each hemisphere controls independent arm, hand, and finger movements contralaterally, but mainly arm movements ipsilaterally. This difference could be observed in splitbrain monkeys executing a visuomotor task with one eye covered, provided tactile guidance of the movements was largely prevented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
1
1

Year Published

1973
1973
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(68 citation statements)
references
References 18 publications
7
59
1
1
Order By: Relevance
“…Because the contralateral M1 is far more active than its ipsilateral counterpart, it can, under normal circumstances, be considered the main controller of hand and finger movements (Gazzaniga 1966;Brinkman and Kuypers 1972). However, our theoretical and empirical results suggest that both M1s are significantly event related in terms of phase locking or, in the case of rhythmic movements, by means of frequency locking.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Because the contralateral M1 is far more active than its ipsilateral counterpart, it can, under normal circumstances, be considered the main controller of hand and finger movements (Gazzaniga 1966;Brinkman and Kuypers 1972). However, our theoretical and empirical results suggest that both M1s are significantly event related in terms of phase locking or, in the case of rhythmic movements, by means of frequency locking.…”
Section: Discussionmentioning
confidence: 70%
“…While early studies on monkeys revealed activations of various cortical areas, including the contralateral primary motor cortex (M1), premotor cortex (PM1), supplementary motor area (SMA), sensorimotor cortex, as well as interhemispheric cross-talk via the corpus callosum (Gazzaniga 1966;Mark and Sperry 1968;Brinkman Correspondence to: A. and Kuypers 1972;Brinkman 1984;Tanji et al 1988), more recent brain-imaging studies identified further contributions of the bilateral secondary somatosensory areas, the basal ganglia, the ipsilateral cerebellum (Deiber et al 1991;Mima et al 1999), and the primary sensorimotor cortex (Kawashima et al 1994;Okuda et al 1995). In spite of this development, however, the derivation of theoretical models providing an encompassing functional interpretation of such data remains a formidable challenge that will occupy neuroscientists for years to come.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the inferiority of the 2-fmger II-hand conditions relative to the l-flnger conditions and the similarity of the I-finger and 4-finger conditions (requiring only one-fourth the scanning distance) indicate that differences in the scanning distance for each finger were not important determinants of reading speed. The evidence for parallel processing of the inputs from the two hands is reminiscent of the suggestions, from studies of men and monkeys in whom the corpus callosum has been sectioned, that the two cerebral hemispheres can function independently as two separate centers for the conscious control of behavior (e.g., Brinkman & Kuypers, 1972;Gazzaniga, 1972). In contrast, the inferiority of the 2-finger / l-hand conditions might be taken to suggest that the middle and index fingers on the same hand compete for common neural pathways.…”
Section: Discussionmentioning
confidence: 90%
“…This bilateral activity in SI is due to the fact that hands and fingers are controlled mainly by the contralateral hemisphere, whereas the arms can also be controlled to a significant degree by the ipsilateral hemisphere (Brinkman and Kuypers, 1972). The agouti usually sits on its HL, leaving the FL free for food manipulation while eating.…”
Section: Callosal Connections Of Agouti Si: Comparisons With Other Mamentioning
confidence: 99%